A critical study on the pre trial process in the juvenile justice system in Malaysia under the Child Act 2001 / Nadzriah Ahmad and Habibah Kiprawi - Ahmad, Nadzriah; Kiprawi, Habibah (Research Management Institute (RMI), 2012)
This research proposal will first discuss the background of the research by highlighting the problems faced by the child offenders at the pre trial process in the juvenile justice system in Malaysia under the Child Act 2001 [hereinafter referred to as the "Child Act"].1 The proposal will then describe the research questions and research objectives which seek to critically examine the issues surrounding the pre trial process in the juvenile justice system under the Child Act in Malaysia and to propose recommendations. The proposal will then highlight the scope of the research and research methodology which will be employed in undertaking the research. It follows that the proposal will outline the foreseeable limitations of the research and describes the contributions that this research will make to the existing body of knowledge on juvenile justice system in Malaysia. Finally, this research will discuss critically the need for a revision of the Child Act…